Resource Allocation Mechanism for Massive MIMO - Christos Bouras; Vasileios Kokkinos; Christina Koulouri (The Sixteenth International Conference on Networking and Services (ICNS 2020), September 27, 2020 - October 01, 2020 , Lisbon, Portugal, 2020)
Nowadays, mobile users need faster data speeds and more reliable service. The next generation of wireless networks 5G pledges to commit that, and much more. Multiple-Input, Multiple-Output (ΜΙΜΟ) technology in 5G networks is studied in this paper, with emphasis on the achieved performance in terms of achieved Bandwidth. Multi-antenna technologies, such as MIMO, are anticipated to play a key role in 5G systems, as they will have to handle much higher speeds than today's cellular networks and greater network traffic. Specifically, we will refer to Massive MIMO (Ma-MIMO) technology. In this paper, a resource allocation mechanism is proposed from the Base Station (BS) to the available antennas, using the Knapsack Problem (KP) algorithm. Our goal is to evaluate user access throughput to the antennas and to study the case where the BS allocates resources, according to the channel rate it receives from each User Equipment (UE). The scenario executed is about serving the maximum number of UE connected to the BS, in high quality services. Finally, we simulate the results in MATLAB, in order to be able to evaluate the Quality of Service (QoS) that is provided to the UE by the BS, with the resource allocation technique that is proposed.